Swot analysis of Institut Perubatan dan Pergigian Termaju, USM and PESTEL about Medical Sector / Muhammad Akmal Danial Muhammad Hassan - Muhammad Hassan, Muhammad Akmal Danial (Universiti Teknologi MARA, Perlis, Faculty of Business and Management, 2021)
My memorable things after I was studying of my diploma and also for my degree is being internship student at Advanced Medical and Dental Institute or Institut Perubatan dan Pergigian Termaju (IPPT). This institute is under Universiti Sains Malaysia (USM). This institute have preclinical centre, clinical centre and also have lab for medical purpose and also have their own lab for Animal Research Centre (ARC). IPPT actually first institute in Asean that own the modern technology and all of that are world class. I am very proud when I got the internship offer here. This IPPT have their own management and not related to the USM. Moreover, they have their own management and their own section to control the IPPT. I have been placed in the finance section under Puan Hafizah and sub to the revenue and assessment unit under Puan Norshahana Binti Che Samsudin. I got really amazing experience there because all the officemates are very kind and sociable. Furthermore, the method that I have been used in this report is SWOT and PESTEL analysis. There were three method that I can be used for this report, but I decided with my advisor to use the SWOT and PESTEL analysis because my company cannot able to give me some data according to their performance and data about them in and out of money. This is because this company were under USM and half under the government. The data were private and confidential. In this method talked about the strengths, weakness, opportunity and threat about this company. The result, I can identify some strengths that really good for the company and also some weakness of the company. About the PESTEL analysis I got some information that many factors impact the medical sector in our country such as from political, environmental, social, technology, economic and legal factor. Many factors help Malaysia to achieve the best level of medical convenience nowadays. Based on the result I see, many strengths and opportunity that can help IPPT to go more further in the future. I recommended that IPPT to take this golden opportunity to create their name internationally with what they owned now.